PARTISIPASI ANGGOTA KELOMPOK TANI DALAM MENUNJANG EFEKTIVITAS GAPOKTAN PADA KEGIATAN PENGUATAN LEMBAGA DISTRIBUSI PANGAN MASYARAKAT DI KABUPATEN BOGOR - Yudhi Harsatriadi Sandyatma (Jurnal Kawistara, 2012)
The study aims at evaluating participation of the Farmer Group Association (Gapoktan) members and factors affecting their participation in the food community Distribution institution program (Penguatan- LDPM). It also examines the impact of the members’ participation on the effectivesness of Gapoktan involvement in the program. The study was conducted in Bogor, West Java. It used mixed methods: qualitative and quantitative. Sampling consisted of 91 respondents and 15 informants. The samplingtechniques used were proportionate strati ed random sampling and purposive techniques, respectively. The results showed that the level of members’ participation in the program was low. Factors that signi cantly affected their participation included age, income, motivation, and intensity of socializationthe activity received. In terms of target achievement, members’ participation has a positive impact on the effectiveness of the association.